2010
DOI: 10.4081/gh.2010.197
|View full text |Cite
|
Sign up to set email alerts
|

Influence of topography on the endemicity of Kala-azar: a study based on remote sensing and geographical information system

Abstract: Abstract. Kala-azar, a fatal infectious disease in many Indian states, particularly in Bihar, West Bengal, Uttar Pradesh, and Jharkhand, is caused by the protozoan parasite Leishmania donovani and transmitted by the sandfly vector Phlebotomus argentipes. The vector is distributed all over the country but the disease is confined to particular zones since before the last century. In this study, parameters such as altitude, temperature, humidity, rainfall and the normalized difference vegetation index (NDVI) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 11 publications
6
62
2
Order By: Relevance
“…In this sense, the knowledge gap which is another drawback in the knowledge-driven approaches was covered in the RBFLN model. Similarly, it has been shown by Bhunia et al (2010) that areas with low altitude, high population density, low vegetation density and low living standard are the most suitable areas for the VL vectors. Sheets et al (2010) also suggested that areas with a low standard of living and with a large number of rainy days are more prone to VL incidence, while Fernandez et al (2010) reported that the distribution of VL vectors is associated with land coverage (bushes and trees) and accessibility to health facility services in densely populated neighbourhoods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the knowledge gap which is another drawback in the knowledge-driven approaches was covered in the RBFLN model. Similarly, it has been shown by Bhunia et al (2010) that areas with low altitude, high population density, low vegetation density and low living standard are the most suitable areas for the VL vectors. Sheets et al (2010) also suggested that areas with a low standard of living and with a large number of rainy days are more prone to VL incidence, while Fernandez et al (2010) reported that the distribution of VL vectors is associated with land coverage (bushes and trees) and accessibility to health facility services in densely populated neighbourhoods.…”
Section: Resultsmentioning
confidence: 99%
“…To specify the input data for the prediction model, the association between VL endemicity and various factors in the literature was explored. In this regard, seven items were deduced from literature to be the critical recognition criteria (CRC) for predictive mapping of VL risk-prone areas: temperature, precipitation, proximity to rivers, altitude, presence of health-centres, land cover and presence of nomads (Sudhakar et al, 2006;Bhunia et al, 2010;Salahi-Moghaddam et al, 2010;Rajabi et al, 2012;Tsegaw et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the distribution of leishmaniasis (i.e., its identification, standardisation, and location) along with monitoring environmental variables with conventional ground surveys is time consuming, laborious and expensive. With increasing accessibility to new technologies, such as remote sensing (RS), it is possible to monitor landuse features on the earth's surface over various time intervals to develop methods for rapid stratification of highly susceptive areas and to design remedial measures (Bakker et al 2000, De La Rocque et al 2004, Mushinzimana et al 2006, Bhunia et al 2010a). Another recent development is the use of satellite data to acquire increasing amounts of geographical data available in conjunction with geographic information systems (GISs) to assist with interpretation of ecosystems and environmental parameters related to sandfly-genic conditions (Sharma & Srivastava 1997, Bergquist 2001, Moore 2008, Bhunia et al 2011 widespread and combined implementation of RS and GIS technology, professionals have been provided with efficient and accurate tools for mapping, maintaining and managing information on landscape features to further our understanding of the epidemiology for the purpose of controlling of VL in India (Palit et al 2001, Sudhakar et al 2006, Bhunia et al 2010b, 2011.…”
mentioning
confidence: 99%
“…Environmental factors that directly influence vector density have previously been shown to be associated with risk for kala-azar (Elnaiem et al, 2003;Sudhakar et al, 2006;Bhunia et al, 2010aBhunia et al, ,b, 2011 Sandy areas Naturally occurring granular material in the river basins <1% 3…”
Section: Discussionmentioning
confidence: 99%
“…Posteriori risk modelling for kala-azar in Africa and Asia suggests that rainfall, altitude and cultivation patterns can predict the transmission rates (Elnaiem et al, 2003;Sudhakar et al, 2006;Bhunia et al, 2010a). Landscape variables such as land use/land cover (LULC) may be particularly important since they are directly linked to vector presence (Feliciangeli et al, 2006).…”
Section: Introductionmentioning
confidence: 99%